Estratégias de extração em química: substâncias húmicas em solos e cobre em cachaça - Oliveira, Andrea Pinto de (Universidade Federal de São Carlos, 2009)
The goal of the extraction strategies here developed was to obtain final products with efficiency and reliability in a time interval as short as possible. The proposed methods are inexpensive and easily applied for different samples. The first extraction strategy proposed deals with humic substances, HS, removal in peat soils aiming the development of an extraction method for organic matter, OM, more efficient and less laborious than the extraction method recommended by IHSS. Alkaline solutions, such as NaOH and Na2CO3, were tested for extracting HS from peat soils followed by purification and drying steps of humic acid, HA. The effect of other experimental variables was investigated aiming to decrease changes in HA molecular structure. It is well known that both molecular structure and physico-chemical properties are critically dependent on the extraction procedure applied for HA in soils. It was also suggested a method for the characterization of functional groups in the HS molecular structure. This study was based on potentiometric titrations carried out at elevated and constant ionic strengths. The conditional dissociation constants, pK s, correspondent to each titrated acidic group were estimated employing tailored computer programs. Some modifications were performed in the conventional Walkley-Black method for the determination of OM content in soils to reach a complete oxidation process. An other extraction strategy developed was the removal of copper(II) ions in cachaça samples employing solid of calcium and magnesium carbonates. The efficiency of this method comes from the ionic exchange between the metal ion and the solid phase of carbonate and also by adsorption phenomena on this solid phase. It was demonstrated that quantitative removal of copper(II) can be reached in a short time mainly for recently distilled cachaça samples.
Extraction in chemistry: humic substances in soils and copper in cachaça
Keywords: Substâncias húmicas; Ácido húmico; Matéria orgânica; Solos; Cachaça; CIENCIAS EXATAS E DA TERRA::QUIMICA